Student communication skills from internalizing religious values to energy modules in life systems - Leny Heliawati; Irvan Permana; Elvi Kurniasih (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2020)
This study aims to analyze the effect of energy modules in life systems on religious values and communication skills. This type of research is a quasi-experimental study with a population of 40 students in grade 7 in SMPN 1 Rumpin, Bogor district. The research design used was a one-group pre-test and post-test. The data obtained were then analyzed using quantitative descriptive. The finding shows that the application of energy modules in living systems effectively internalizes the religious values of students based on the average n-gain of 0.49 which is included in the medium category. Students’ communication skills reach a good category with a score of 78%. The study concludes that the energy module in living systems effectively internalizes religious values and students’ communication skills.